Analisis Pengaruh Strategi Promosi, Citra Merek, dan Kualitas Layanan Terhadap Keputusan Menginap Tamu di Hotel Grasia Semarang - Dita Aulia Rachma Nurul Farida; Nina Mistriani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to analyze the effect of promotional strategies, brand image, and service quality on guests' decision to stay at Hotel Grasia Semarang. The intense competition in the hospitality industry requires hotels to implement effective marketing strategies to attract guests. Factors such as attractive promotions, a strong brand image, and good service quality are key considerations in guests' decision-making process. This research uses a quantitative approach with surveys as the data collection method, where 100 respondents, who are guests of Hotel Grasia Semarang, were selected using purposive sampling. The collected data were analyzed using multiple linear regression to examine the relationship between the independent variables (promotion, brand image, service quality) and the dependent variable (decision to stay). The results of the study indicate that these three factors have a significant effect on guests' decision to stay at the hotel. The implication of these findings is the importance for hotel management to strengthen the brand image, offer appropriate promotions, and improve service quality to enhance guest satisfaction and loyalty. This study contributes to the development of marketing strategies in the hospitality industry, particularly at Hotel Grasia Semarang.